MEMBANGUN SEMANGAT KERASULAN REMAJA KATOLIK DALAM KONTEKS MASYARAKAT PLURALIS DI INDONESIA - Agustinus Supriyadi (Bahasa Indonesia, 2017)
Catholic teens Indonesia is part of the Church in Indonesia and the Indonesian people. Indonesia consists of thousands of islands that stretched from Sabang to Merauke. This fact opens the possibility of a fairly wide occurrence of the encounter between cultures and simultaneous cross-cultural. This diversity is certainly a logical consequence to an enrichment of civilizations and diversity (plurality), although also contains elements of the loss. Plurality of Indonesian society on the one hand can make the Catholic teens swept away in the swift currents of the community to lose our identity or conflict. However Plurality can also awaken in the Catholic teen award nature between one race to the other races, between ethnic or tribal one with the other tribes, between groups with one another. In a pluralistic society such as this, the Catholic teens called to the apostolate. Through the act of self-discovery, live in love and have a sense of tolerance of differences is the real form of the apostolate.